The Effect of The Addition of Mealworm Frass (Tenebrio Molitor) and Molasses on the Increasing of the Proximate Value of White Oyster Mushroom (Pleurotus Ostreatus) - Mentari Jelita Putri; Andi Faridah Arsal; Halifah Pagarra; Rachmawaty Rachmawaty; Andi Asmawati Asiz; Alimuddin Ali; Abd Muis; Muhammad Junda; Yasser Abd Djawad; Oslan Jumadi (bionature, 2023)
This study aims to determine the effect of the addition of mealworm frass and molasses on the proximate value of white oyster mushrooms. This type of research was an experiment using a completely randomized design (CRD) consisting of four treatments with three replications each. Test parameters include water content, ash content, crude protein, crude fat and crude fiber. Proximate data on water content, ash content, crude protein, crude fat and crude fiber were analyzed using analysis of variance (ANOVA) and Tukey's follow-up test with a 95% confidence level. The results showed that treatment with frass and frass molasses had an effect on water content, ash content, crude protein, crude fat, and a decrease in fiber content. Therefore, it can be concluded that the addition of mealworm frass and molasses affects the proximate value of the resulting oyster mushrooms.Keywords: White Oyster Mushroom, Flour Caterpillar Frass, Molasses, Proximate.